1969
DOI: 10.1136/thx.24.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular septal defect and aortic regurgitation

Abstract: We have reviewed our experience of 29 patients with the association of ventricular septal defect and aortic regurgitation, 27 of whom have been treated surgically. Our present approach to the surgical management is outlined and the embryology and pathological anatomy are reviewed. The most common cause of aortic regurgitation was a prolapsed aortic valve cusp, which occurred in 19 patients. Aneurysmal dilatation of an aortic sinus accounted for the regurgitation in three patients, and two patients had both abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…H a l l i d i e -S m i t h el al. [14] found in 29 patients, 27 of whom were treated surgically, a systolic pressure gradient below the pulmonary valve or high in the body of the right ventricle of more than 20 mm Hg in 12 cases. Three of these patients had hypertrophy of the infundibulum requiring resection, in the remaining 9 patients, however, the pressure gradient disappeared after closure of the ventricular septal defect and repair of the aortic insufficiency, suggesting it might have been caused by prolapse of an aortic leaflet and/or sinus into the infundibulum.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…H a l l i d i e -S m i t h el al. [14] found in 29 patients, 27 of whom were treated surgically, a systolic pressure gradient below the pulmonary valve or high in the body of the right ventricle of more than 20 mm Hg in 12 cases. Three of these patients had hypertrophy of the infundibulum requiring resection, in the remaining 9 patients, however, the pressure gradient disappeared after closure of the ventricular septal defect and repair of the aortic insufficiency, suggesting it might have been caused by prolapse of an aortic leaflet and/or sinus into the infundibulum.…”
Section: Discussionmentioning
confidence: 96%
“…6 of his 7 angiocardiographically diagnosed cases of supracristal defects were confirmed by surgery. H a l l i d i e -S m it h et al [14] found an intracristal localization in 20 of 27 cases operated on for ventricular septal defect coincident with aortic regurgitation and a supracristal localization in 7.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation